Role of pseudohypoxia in the pathogenesis of type 2 diabetes - Song, Jing (Hypoxia (Auckl), 2019)
Type 2 diabetes is caused by persistent high blood glucose, which is known as diabetic hyperglycemia. This hyperglycemic situation, when not controlled, can overproduce NADH and lower nicotinamide adenine dinucleotide (NAD), thereby creating NADH/NAD redox imbalance and leading to cellular pseudohypoxia. In this review, we discussed two major enzymatic systems that are activated by diabetic hyperglycemia and are involved in creation of this pseudohypoxic condition. One system is aldose reductase in the polyol pathway, and the other is poly (ADP ribose) polymerase. While aldose reductase drives overproduction of NADH, PARP could in contrast deplete NAD. Therefore, activation of the two pathways underlies the major mechanisms of NADH/NAD redox imbalance and diabetic pseudohypoxia. Consequently, reductive stress occurs, followed by oxidative stress and eventual cell death and tissue dysfunction. Additionally, fructose formed in the polyol pathway can also cause metabolic syndrome such as hypertension and nonalcoholic fatty liver disease. Moreover, pseudohypoxia can also lower sirtuin protein contents and induce protein acetylation which can impair protein function. Finally, we discussed the possibility of using nicotinamide riboside, an NAD precursor, as a promising therapeutic agent for restoring NADH/NAD redox balance and for preventing the occurrence of diabetic pseudohypoxia.